Venezia e il Peloponneso, 992-1718 : indagini storiche tra territorio, biblioteca e archivio - Nanetti, Andrea (Edizioni Ca’ Foscari, 2022)
The extraordinary wealth of archival documents, chronicles, travel reports, archaeological sites and monuments, still for the most part to be studied, makes the privileged relationship between Venice and the Peloponnese a key element for the study of Venetian society, with reference to choices made by Venetians in the search for an ethical relationship with the Other in the geopolitical pursuit of their constitutional aim, i.e. far la marchadantia pacifichamente (to trade peacefully). In an almost millenary chronology (992-1718), the Peloponnese – a land on the maritime border between the Ionian and the Aegean Seas, a cultural and commercial link between the Latin-Roman West and the Hellenistic East – is a privileged laboratory for the training of the next generation of interdisciplinary and cross-cultural historians, and for staunch supporters of peace among peoples.